On the Prototypes and Chronology of Buildings of the Last Period of Medieval Serbian Architecture (Some Remarks on the Historiography) - Maltseva, Svetlana V. (Actual Problems of Theory and History of Art, 2013)
The article is devoted to the main issues arising in the process of studying the Moravian period of the Serbian medieval architecture. The following themes are highlighted as being among the most important: the general classification of the Serbian medieval architecture, the definition of the main trends and logics of its development, the determination of the regional specifics of the Serbian architecture in the 14th ‒15th cc., and finally, the discovering of its character and degree of its dependence on the general processes in the development of the Byzantine architecture of the Paleologean period. Inter alia, the various hypotheses are considered, which were introduced by the scholars in order to explain the origin of the specific typology of the Moravian triconch churches.
Keywords: Serbian medieval architecture; Byzantine architecture; periodization of the Serbian medieval art; triconch; Moravian school; Moravian architecture; historiography of the Serbian medieval architecture